Effectiveness of post-partum family planning interventions on contraceptive use and method mix at 1 year after childbirth in Kinshasa, DR Congo (Yam Daabo): a single-blind, cluster-randomised controlled trial - Nguyen Toan Tran, MD; Armando Seuc, PhD; Béatrice Tshikaya, MSc; Maurice Mutuale, MSc; Sihem Landoulsi, MSc; Brigitte Kini, MD; Bernadette Mbu Nkolomonyi, MD; Jean Nyandwe Kyloka, MD; Félicité Langwana, MSc; Asa Cuzin-Kihl, MSc; James Kiarie, MD; Mary Eluned Gaffield, PhD; et al. (Elsevier, 2020)
Summary: Background: In rural Burkina Faso, a package of six low-technology, post-partum contraceptive interventions (ie, refresher training for providers, a counselling tool, supportive supervision, daily availability of contraceptive services, client appointment cards, and invitation letters to attend appointments for partners), aimed at strengthening existing primary health-care services and enhancing demand for them, doubled the use of modern contraceptives at 12 months post partum (ie, 55% uptake in intervention recipients vs 29% in routine-care users). This study assessed the effect of a similar package but in urban settings of Kinshasa province, Democratic Republic of the Congo, in an effort to reduce the unmet need for post-partum family planning. Methods: Yam Daabo was a multi-intervention, single-blinded, cluster-randomised controlled trial done in six primary health-care centres (clusters) in Kinshasa. Centres were randomly allocated to receive the six-component intervention or standard antenatal and postnatal care in matched pairs (1:1) on the basis of number of monthly births, the ratio of health workers per population in the health zone, and the urban and suburban settings. Only data analysts could be masked to cluster allocation. Health-care facilities were eligible if they provided a continuum of antenatal, delivery, and postnatal care, were well stocked with contraceptives, and were situated close to the main study centre. All pregnant women presenting to the six centres were eligible if they were in their third pregnancy trimester and had no counterindications to deliver in the facility. The main outcome was prevalence of use of modern contraceptives at 12 months after delivery. Analysis was by modified intention-to-treat using generalised linear mixed models or Fisher's exact test for small groups. Prevalence ratios were adjusted for cluster effects and baseline characteristics. This study was registered with the Pan-African Clinical Trials Registry (PACTR201609001784334). Findings: From July 1, 2016, to Feb 2, 2017, eight of 52 clinics assessed for eligibility met the criteria and were randomised. Of 690 women approached, 576 (83%) women were enrolled: 286 in the four intervention clusters and 290 in the four control clusters. Of them, 519 (90%) completed the 12-month study exit interview (252 in the intervention group and 267 in the control group) and were included in the intention-to-treat analysis. At 12 months, 115 (46%) of 252 women in the intervention group and 94 (35%) of 267 in the control group were using modern contraceptives (adjusted prevalence ratio [PR] 1·58, 95% CI 0·74-3·38), with significant differences in the use of contraceptive implants (22% vs 6%; adjusted PR 4·36, 95% CI 1·96-9·70), but without difference in the use of short-acting contraceptives (23% vs 28%; 0·92, 0·29-2·98) and non-modern or inappropriate methods (7% vs 18%; 0·45, 0·13-1·54). There were no serious adverse events or maternal deaths related to the study. Interpretation: The Yam Daabo intervention package did not have a significant effect on the overall use of effective modern contraceptives but significantly increased implant use in women post partum who live in urban settings in Kinshasa up to a year after childbirth. However, interferences from external family planning initiatives in the control group might have diminished differences between the services received. Such an intervention could be potentially relevant in similar contexts in DR Congo and other countries. Funding: Government of France; UNDP/UNFPA/UNICEF/WHO/World Bank Special Programme of Research, Development and Research Training in Human Reproduction.